LABORATORY METHODS FOR THE DETECTION OF MARKERS OF HEMOTRANSMISSIVE INFECTIONS IN BLOOD DONORS - Kurbonova Zumrad Chutbayevna; Samatova Lobar Dilmurodovna; Saidov Alonur Baxtinurovich; Matkarimova Dilfuza Soburovna; Bobojonova Shoxista Davronbekovna (The Bioscan, 2025)
New laboratory diagnostic capabilities, as well as vaccination of the population against blood-borne infections and inactivation of the virus in donor plasma can reduce the risk of infections in recipients after transfusion. The article examines modern methods of virus inactivation to ensure the infectious safety of donor blood. KEYWORDS: Blood donors, hemotransmissive infections, laboratory diagnostics, serological testing, PCR, ELISA, blood screening, infectious markers, transfusion safety